Pengaruh Model Pembelajaran Terhadap Hasil Belajar Chest Pass Permainan Bola Basket Ditinjau Dari Motivasi Belajar Peserta Didik - Amiariasti, Ni Kadek; Sudiana, I Ketut; Dharmadi, Made Agus; Semarayasa, I Ketut; Lesmana, Kadek Yogi Parta (Jurnal Sporta Saintika, 2024)
Skills competency is one aspect that must be achieved in learning. However, sometimes this cannot be achieved due to inappropriate learning strategies. This research aims to determine the effect of STAD type cooperative learning assisted by visual fedback on the learning outcomes of basketball game chest passes in terms of students' learning motivation. This research uses a quasi-experimental method using a post-test only control group design. The population is 358 students in class The sampling technique uses random sampling with random groups to determine the experimental and control classes. The samples in each cell were 19 people. Data was collected through tests and analyzed using two-way Anova analysis followed by the LSD test. The results of the research show that the STAD type cooperative learning model assisted by visual feedback has a significantly better impact on learning outcomes for chest passes in the game of basketball compared to learning outcomes using conventional models. There was an interaction between the learning model and learning motivation, where it was found that the STAD cooperative learning model assisted by visual feedback was more suitable for students with high learning motivation, but on the other hand, low learning motivation was more suitable for using the conventional model. It is concluded that the STAD type cooperative learning model can improve learning outcomes for chest passes in basketball in high school